Effect of Electron-Beam Irradiation on Microbiological Safety, Nutritional Quality, and Structural Characteristics of Meat - Duman Orynbekov; Kumarbek Amirkhanov; Zhanar Kalibekkyzy; Nazerke Muslimova; Gulnur Nurymkhan; Almagul Nurgazezova; Samat Kassymov; Amirzhan Kassenov; Aigul Maizhanova; Botakoz Kulushtayeva; Zhanibek Yessimbekov (Foods)
Foodborne pathogens remain a significant global challenge, contributing to widespread illness and considerable food losses. This study investigates the effects of electron-beam irradiation on beef quality and safety using a pulsed high-frequency linear accelerator (ILU-10). Meat samples were subjected to irradiation at doses of 3, 6, and 9 kGy, with non-irradiated samples serving as controls. The research focused on evaluating microbial reduction, alterations in textural properties, and changes in nutritional components including amino acids, vitamins, and mineral content. Microbiological analysis demonstrated a dose-dependent reduction in total viable counts, with a decrease from 300 CFU/g in controls to 100 CFU/g at 3 and 6 kGy and complete microbial inactivation at 9 kGy. Scanning electron microscopy revealed disruption in myofibrillar structure, with increased interstitial spacing. Chemical analyses indicated a dose-dependent decline in total amino acid content and variable responses among individual amino acids, suggesting irradiation-induced protein fragmentation and oxidation. The findings suggest that, when optimized, irradiation can substantially improve meat safety while maintaining acceptable nutritional and sensory quality.